UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN MENERAPKAN METODE KOOPERATIF MODEL JIGSAW PADA SISWA KELAS V MI MIFTAHUL HUDA PUCANGAN MONTONG TUBAN TAHUN PELAJARAN 2017/2018 - Nurlaili Dina Hafni; Muflihatun Nisa’ (PREMIERE : Journal of Islamic Elementary Education, 2019)
This research is motivated by the fact that the still low learning outcomes of Social Sciences subjects in fifth grade MI Miftahul Huda Pucangan students. Possible learning methods that can affect student achievement are the cooperative jigsaw model. The problem of this research is to explain the efforts to improve learning outcomes of social science by applying the cooperative jigsaw method. The theories used in the conduct of this research include LAN about learning outcomes, social science and the cooperative jigsaw model method. This research is expected to provide answers to the formulation of the problem (1) How is the application of the jigsaw cooperative method in the learning process of social science in class V MI Miftahul Huda Pucangan Montong Tuban in the academic year 2017/2018? and (2) Can the cooperative jigsaw method improve social studies learning outcomes for fifth grade MI Miftahul Huda Pucangan Montong Tuban students in the 2017/2018 academic year? This type of research is classroom action research (CAR). The subjects of this study were 36 grade V students, consisting of 18 boys and 18 girls. This research lasted for 2 cycles. For data collection techniques used observation techniques and data collection tools in the form of test questions. The collected data is then analyzed using a data processing method with descriptive statistical analysis which presents the data in the form of tables and bar charts. Then presented in each cycle to get information (observations), both from data collected from observation sheets and written tests. The results of the study in the first cycle showed the average percentage of teacher activity in the first cycle meeting 1 78% and 2% meetings 86%, while in the second cycle 1 meeting 90% and 95% meetings 2. In addition to teacher activity, student activity in groups also increased, in cycle I meeting 1 the percentage of student activity was 68% and meeting 2 was 77%, whereas in cycle II at meeting 1 the percentage increased 80% and meeting 2 90%. Social studies learning outcomes in pre-cycle with an average value of 68.94 and classical completeness of 42%, the first cycle obtained an average value of 78.27 with classical completeness of 78%. In the second cycle learning outcomes increased with an average value of 82.61 with 92% mastery learning. Means that at the end of the second cycle it has been shown that classical learning completeness is in accordance with indicators of success. The results of these studies can be concluded, that by using the cooperative jigsaw model can increase teacher activity in managing learning and student activities in the learning process. Student learning outcomes in social studies lessons increase in accordance with predetermined minimal completeness criteria standards.